Metabiotic Medicine of Symbiotic Corynebacteria: Prevention, Treatment and Immunological Safety - E. A. Shmeleva; A. E. Vershinin; S. S. Andina (Эпидемиология и вакцинопрофилактика)
Relevance. Acute respiratory diseases (ARD) occupy a leading position in infectious pathology. Patients who often suffer from the acute respiratory diseases, in most cases have an ENT pathology against the background of immunodeficiency state. Large groups of people are often affected by such diseases. As a rule, the causative agents of such diseases are pathogenic and conditionally pathogenic microorganisms. To solve this problem, therapeutic immunomodulatory vaccines have been proposed. The goal of such drugs is to enhance specific resistance to a large number of conditionally pathogenic microorganisms. Aims. The purpose of this work is to demonstrate the prophylactic, therapeutic efficacy and immunomodulating safety of a metabiotic preparation produced from symbiotic corynebacteria. Materials and methods. A medicine Kodivak, a structural component of the cell wall of the symbiotic corynebacterium (Corynebacterium diphtheriae (tox +) was used in the work. The study on long term Cd tox + bacteria carriers examined the therapeutic efficacy as well as immunomodulating safety of Kodivak compared with some vaccines. Results and discussion. All carriers who have undergone the treatment with Kodivak stopped the release of Cd tox +, which was confirmed by a bacteriological analysis, and the condition of the oropharynx corresponded to the physiological norm. The quantitative indicators of the content of lymphocytes in the blood of the long-term carriers of C. diphtheriae tox + were determined before and after the course of treatment with Kodivak. Selective immunocorrecting effect of Kodivak on the human immune system is shown. A comparative analysis of post-vaccination changes in the number of immunocompetent cells of patients immunized with different vaccines showed that medicines containing antigens that are responsible for pathogenicity stimulate the state of immunodeficiency at a certain stage. While Kodivak does not cause significant deviations in the composition of the subpopulation of lymphocytes from the physiological norm. Conclusions. The findings confirm the possibility and necessity of using Kodivak not only for the rehabilitation of long-term carriers, but also both for therapeutic and prophylactic purposes in the risk groups of ARD morbidity of microbial and viral etiology as well as a nonspecific immunomodulating agent for the restoration of microsymbiogenesis in the upper respiratory tract biotopes.